The Use of Mobile Applications for Enhancing English Pronunciation Skills - Jovliyeva Nafosat Bahodir qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Annotation: This article examines the effectiveness of mobile applications in improving English pronunciation skills among EFL learners. With the growing use of smartphones and educational technology, mobile-assisted language learning (MALL) has become an important tool in modern English language education. The study discusses how mobile applications such as ELSA Speak, Speechling, and Duolingo can enhance learners’ pronunciation through real-time feedback, repetition, and interactive practice. It also highlights the advantages of mobile learning, including accessibility, flexibility, and learner autonomy. The findings show that integrating mobile applications into English classes can significantly improve learners’ pronunciation accuracy, confidence, and motivation.